Avian influenza overview September – December 2021. (23rd December 2021) - ,; Adlhoch, Cornelia; Fusaro, Alice; Gonzales, José L; Kuiken, Thijs; Marangon, Stefano; Niqueux, Éric; Staubach, Christoph; Terregino, Calogero; Aznar, Inma; Muñoz Guajardo, Irene; Baldinelli, Francesca
Abstract: Between 16 September and 8 December 2021, 867 highly pathogenic avian influenza (HPAI) virus detections were reported in 27 EU/EEA countries and the UK in poultry (316), in wild (523) and in captive birds (28). The detections in poultry were mainly reported by Italy (167) followed by Hungary and Poland (35 each). Tha majority of the detections in wild birds were reported by Germany (280), Netherlands (65) and United Kingdom (53). The observed persistence and continuous circulation of HPAI viruses in migratory and resident wild birds will continue to pose a risk for the poultry industry in Europe for the coming months. The frequent occurrence of HPAI A(H5) incursions in commercial farms (including poultry production types considered at low avian influenza risk) raises concern about the capacity of the applied biosecurity measures to prevent virus introduction. Short‐term preparedness and medium‐ and long‐term prevention strategies, including revising and reinforcing biosecurity measures, reduction of the density of commercial poultry farms and possible appropriate vaccination strategies, should be implemented. The results of the genetic analysis indicate that the viruses characterised during this reporting period belong to clade 2.3.4.4b. Some of the characterized HPAI A(H5N1) viruses detected in Sweden, Germany, Poland and United Kingdom are related to the viruses which have been circulating in Europe since October 2020; in North, Central, South and East Europe novel reassortant A(H5N1) virus has been introduced starting from October 2021. HPAI A(H5N1) was also detected in wild mammal species in Sweden, Estonia and Finland; some of these strains characterised so far present an adaptive marker that is associated with increased virulence and replication in mammals. Since the last report, 13 human infections due to HPAI A(H5N6) and two human cases due to LPAI A(H9N2) virus have been reported from China. Some of these A(H5N6) cases were caused by a reassortant virus of clade 2.3.4.4b, which possessed an HA gene closely related to the A(H5) viruses circulating in Europe. The risk of infection for the general population in the EU/EEA is assessed as low, and for occupationally exposed people, low to medium, with large uncertainty due to the high diversity of circulating viruses in the bird populations.